What is the impact of providing a transcatheter aortic valve implantation service on conventional aortic valve surgical activity: patient risk factors and outcomes in the first 2 years. Issue 20 (11th October 2010) - Grant, S W; Devbhandari, M P; Grayson, A D; Dimarakis, I; Kadir, I; Saravanan, D M T; Levy, R D; Ray, S G; Bridgewater, B
Abstract : Objectives: To assess the impact of introducing a transcatheter aortic valve implantation (TAVI) service on aortic valve surgical activity and outcomes. Design: A retrospective analysis of prospectively collected data. Setting: University hospital of south Manchester. Patients: 815 consecutive patients undergoing isolated aortic valve replacement (AVR) or coronary artery bypass grafting plus AVR from January 2006 to December 2009. Fifty consecutive patients who underwent TAVI from January 2008 to December 2009. Main outcome measures: Aortic valve surgical activity in the 2 years before the introduction of a TAVI service and in the 2 years following. Outcomes following conventional aortic valve surgery and TAVI. Results: In the 2 years following the introduction of TAVI at this centre, conventional AVR activity has increased by 37% compared with an 8% increase nationally (p<0.001). Compared with the 2 years before TAVI there was no change in the mean logistic EuroSCORE (7.4 vs 7.9 p=0.16) or crude mortality rate (2.9% vs 2.1% p=0.48). Fifty high-risk patients underwent TAVI with a 30-day mortality rate of 0%. The mean logistic EuroSCORE of the TAVI patients was 25.3. Conclusions: TAVI is an emerging alternative to AVR in high-risk patients. Since the introduction of a TAVI service at this centre, conventional AVR activity has increased. Despite a trend of increasing mean logistic EuroSCORE indicating that more complex cases are being undertaken, there has been a non-significant reduction in the crude mortality rate. Offering a TAVI service has a positive impact on the volume of conventional AVR surgical activity.